Natural resources, institutions, and economic transformation in Mozambique - José Jaime Macuane; Carlos Muianga (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
In the light of Mozambique's natural resources boom-especially its large-scale investments in mining, oil, and gas-this paper analyses the prospects for the extractive industries to contribute to economic transformation from an institutional perspective. To this purpose, we address the institutional dynamics of the resources sector and consider the underlying causes of the identified outcomes. The National Development Strategy, as the instrument presenting the vision for economic transformation and diversification, is discussed. The paper is based on a desk review-documental and bibliographic-and on primary data gathered by the authors as part of their research into the field of natural resources and the political economy of development. We conclude that, given Mozambique's political patronage and clientelism, intra-ruling elite competition, limited productive base, weak state capacity, high level of poverty, and recurrent fiscal deficits, the prospects of the current resource boom leading to economic transformation, despite its considerable potential, are at best uncertain.
Keywords: O13; O23; O25; O43; 330; economic transformation; extractive industries; institutions; Mozambique; naturalresources